2021
DOI: 10.3389/fpsyg.2020.615341
|View full text |Cite
|
Sign up to set email alerts
|

A Rasch Analysis of the Irrational Procrastination Scale (IPS)

Abstract: The present study analyses the psychometric properties of the irrational procrastination scale (IPS; Steel, 2002, 2010) in a sample of United States college students using the Rasch modeling approach. Results showed that the IPS items had a high level of reliability, good content validity, structural validity, and substantive validity, and no differential item functioning (DIF) effects in terms of gender. The IPS was found to be unidimensional, supporting the originally proposed theoretical structure by Steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…In sum, as an initial validation study, our paper presented preliminary validity evidence supporting the use of the IPS in the Chinese context. The findings are in accordance with conclusions from studies that corroborated the psychometric soundness of the IPS in other countries (e.g., Svartdal et al, 2016 ; Svartdal, 2017 ; Guilera et al, 2018 ; Kim et al, 2020 ; Shaw and Zhang, 2021 ). At present, there has been accumulated evidence globally that suggests the utility of the IPS as a brief and valid scale for assessing procrastination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In sum, as an initial validation study, our paper presented preliminary validity evidence supporting the use of the IPS in the Chinese context. The findings are in accordance with conclusions from studies that corroborated the psychometric soundness of the IPS in other countries (e.g., Svartdal et al, 2016 ; Svartdal, 2017 ; Guilera et al, 2018 ; Kim et al, 2020 ; Shaw and Zhang, 2021 ). At present, there has been accumulated evidence globally that suggests the utility of the IPS as a brief and valid scale for assessing procrastination.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous research (e.g., Steel, 2010;Rozental et al, 2014;Svartdal et al, 2016;Svartdal and Steel, 2017;Guilera et al, 2018), we found adequate internal consistency reliability of the nine-item scale within this sample. Regarding the dimensionality, the CFA results confirmed the one-factor structure of the IPS, which fit well with the original idea of the scale (as a unidimensional measure of irrational procrastination) put forward by Steel (2010Steel ( , 2002 as well as conclusions from prior validation studies in other languages and countries/regions (e.g., Svartdal et al, 2016;Svartdal, 2017;Kim et al, 2020;Shaw and Zhang, 2021). Furthermore, measurement invariance held across gender, demonstrating that the Chinese IPS was not biased against men or women and that any gender difference in the scale scores would be attributable to the underlying psychological construct itself.…”
Section: Discussionsupporting
confidence: 84%
“…The IPS is used to assess the changes from pre-to postscores. The IPS showed good internal consistency (Cronbach α=.91) [50] as well as a high level of reliability (r pm =0.58-0.74), and good content, structural, and substantive validity [51].…”
Section: Procrastination Tendenciesmentioning
confidence: 94%
“…For academic stress, the Student-Life Stress Inventory-Revered (SLSI) proposed by Gadzella ( 2005) is used, subsequently producing a Cronbach alpha value of .93. Furthermore, the PWS (Psychological Well-Being Scale) and IPS (Irrational Procrastination Scale) proposed by Ryff (1989) and Shaw & Zhang (2021) are used for psychological well-being and procrastination, respectively. In this case, the development of these measuring instruments is thoroughly compiled, regarding the observed determinants.…”
Section: Introductionmentioning
confidence: 99%